Decoration in Islamic architecture - Spahic, Omer (International Islamic Publishing House (IIPH), 2020)
Allah is beautiful and loves beauty. Hence, in His creation of this universe, one beholds the highest standard of magnificence, symmetry and order. Allah has bestowed humankind with an aesthetic sense that helps them design and create architecture that adequately translates the true essence of His divine infinity and perfection. Islamic architecture and decoration, therefore, leads one to contemplate on Allah, His Oneness and His innumerable bounties. From the simple building structure of the early days of Islam till the majestic edifices of the present era, each and every architectural endeavour reflects the interests and engagements of Muslims as Allah’s trustees on the earth. Tracing the history of the building activities of the Muslims and the way different modes of decoration were added to the simple structures over a period of time, the author brings home the point that construction and beautification should be inspired by the heavenly message of Islam and its dynamic spirit. If this criterion is not observed, genuine Islamic architecture will cease to exist. Many have debated the permissibility of decorating buildings especially those that serve a religious purpose, namely mosques and Islamic schools. However, since Islam opposes neither artistic creativity nor the enjoyment of beauty, decorating edifices is allowed if the objectives of Islamic jurisprudence are strictly adhered to. In such a scenario, the deed not only becomes acceptable but laudable as well.